ELEVATING THE COMPETITIVENESS OF MICRO, SMALL, AND MEDIUM-SIZED ENTERPRISES IN CIHERANG VILLAGE THROUGH BUSINESS MENTORSHIP - Farisadri Fauzan; Rivani Rivani; Linda Kurniawati; Luthfi Thirafi (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2022)
Micro, small, and medium-sized enterprises (MSMEs) were affected by the coronavirus disease (Covid-19) outbreak. About 82.9% of MSMEs were negatively affected. As a result, there were significant changes in running a business. The use of technology has become crucial and needed by the MSMEs to survive the pandemic’s economic effect. Nevertheless, human resources in a village lack the knowledge of using technology to digitalize their business. MSMEs in Ciherang Village are among many MSME located in a village affected by the pandemic. Therefore, mentorship for MSMEs in Ciherang Village is crucial to ensure the MSME could survive and grow. According to the data from observation, some problems occur on the MSMEs in Ciherang Village: legalities, packaging, product picture, and knowledge to leverage the internet marketing. By mentorship, the MSMEs in Ciherang Village benefited and could implement the new things they learn in their business. At the end of the activity, the mentees have their Business Registration Number (Nomor Induk Berusaha – NIB), good packaging, good product pictures, and knowledge to leverage internet marketing